Rancang Bangun Sistem Kontrol Elektro Pneumatik Pada Alat Penumbuk Hitanol - Ardiansyah, Ahmad Yusuf; Wirawan, Surya (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2024)
Hitanol is a granular chemical that is used as a raw material to make compound bladders. The manufacturing process of compound bladder starts by weighing the chemicals. Before the weighing process, hitanol undergoes an agglomeration or accumulation of particles that causes hitanol to agglomerate and makes it difficult for the operator to weigh. As a result, operator has to do the crushing process so that the hitanol returns to granular form. The crushing process is currently being done manually by hitting the hitanol using iron stick. These problems were a driving force in the design of the hitanol crusher with an electro pneumatic system. The results of the design of the hitanol crusher using a double acting cylinder with a stroke length of 250 mm controlled by electric signal. The air flow in the pneumatik cylinder is controlled by a 5/2 single coil solenoid valve that triggered by timer and relay.